Relationship between bullying behaviours and sleep quality in school-aged children - Gomes, A. M. (2021)
Do children who practice bullying have more sleep disturbances than those who do not practice bullying? The research questions for this study were 1)Are there are differences in sleep quality between aggressors and non-aggressors and between victims and non-victims? 2)Do aggressors have higher SDI than non-aggressors?3)What are the sleep characteristics in aggressors, non-aggressors, victims and non-victims?The purpose of the study was to analyse whether school-agedchildren who practice bullying have worse sleep quality than those who do not practice it and to identify the characteristics of dysfunctional sleep for aggressors?The research method was a cross-sectional study focusing on quantitative methodology. We analysed and compared the results of two questionnaires: bullying, aggressiveness among children with n= 1109, answered by the children and the Children’s Sleep Habits Questionnaire (CSHQ), with n= 883, answered by the parents. A convenience sample of 8 state and private schools in Portugal was worked upon.The SDI of aggressorsis not significantly different from the SDI of non-aggressors. In the 33 CSHQ items, in seven the aggressors manifest significant differences: they go to bed at the same time less often, "fight" going to bed, sleep poorly, wet the bed more often, have a more agitated sleep, wake up with nightmares and are grumpier.There are no differences between the two groups, as both have high SDI. In the aggressors, the SDI is accentuated in relation to non-aggressors with regard to the following: more difficulty in going to bed at the same time, fight more at bedtime, sleep less, wet the bed, have more agitated sleep, wake up with nightmares more and wake up grumpy.